The Latin Language as a Universal Cultural Code - Korolova, Nataliia; Koshchii, Oksana; Myronova, Valentyna (Journal of History Culture and Art Research, 2019)
The article deals with the phenomenon of Latin as a universal cultural code that continues to be actively used in various spheres of life. Knowledge of Latin not only facilitates the study of many languages, but also allows to attach oneself to the world cultural values, promotes the establishment of links between Latin, ancient culture, and European civilization, gives access to the perception and understanding of works of literature and painting, enhances general erudition and professional competence, expands the cultural horizons. Using non-traditional linguo-cultural forms enables to form traditional ideas about the subject, and to synthesize the information received, integrate it into the modern world and start the replication process in real life situations. The formation of a holistic view of the world around involves not only mastering a number of special disciplines of the chosen specialty, but also the awareness of the connection between them, the addition of one science to another. That is why the use of the interdisciplinary approach is a prerequisite for the organization of the educational process. The interdisciplinary approach allows us demonstrating the ways of meaningful use of the gained knowledge and providing an exhaustive answer to the question: Why should I know this? What is the benefit of this? Where can I apply it?